From Reconstruction to Resilience: The Evolution of Crisis Management in Indonesia’s Political Leadership - Asqori Pohan, Ibnu (Iapa Proceedings Conference, 2025)
This study examines the crisis management strategies employed by Presidents Susilo Bambang Yudhoyono (Yudhoyono) and Joko Widodo (Jokowi) in addressing two significant national crises: the 2004 Aceh tsunami and the COVID-19 pandemic. This research uses qualitative approaches and secondary data analysis to explore how individual leaders navigate crises through decision-making, public engagement, and policy implementation. The findings reveal differences in leadership styles and strategic priorities. Yudhoyono adopted a post-disaster reconstruction model, emphasizing international collaboration, large-scale infrastructure rehabilitation, and institutional reforms to improve disaster preparedness. Instead, Jokowi prioritized rapid response measures, focusing on public health interventions such as mass vaccination programs and social protection policies to mitigate the economic impact of the pandemic. A comparative analysis reveals that the effectiveness of crisis leadership is influenced by factors such as policy adaptability, institutional coordination, and resource mobilization. While Yudhoyono’s approach is long-term and institutionally structured, Jokowi’s crisis management is characterized by real-time policy adjustments and direct public involvement. This study contributes to the discourse on political leadership and crisis governance, demonstrating how different leadership approaches impact national resilience and crisis management outcomes. The findings suggest that future leaders should adopt a balanced strategy that integrates long-term resilience planning with proactive, flexible, and inclusive crisis response mechanisms.